Freie Stadt Danzig - Danziger Verkehrszentrale; Verlag W. F. Burau (Gdańsk). (Danzig : W. F. Burau, 1930)
Folder turystyczny.
Data na podst. treści.
Keywords: Turystyka -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Gdańsk (Polska) -- 1900-1945 -- druki ulotne